Core introduction - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
After completing this program, the trainees should be able to identify functional elements and components, define terminology and explain field device and controller operation.
Keywords: Engineering instruments; Automatic control; Control theory